Diseño e implementación de un modelo instruccional educativo en un entorno virtual de aprendizaje abierto regido bajo el modelo ADDIE, dirigido a niños con habilidades especiales en el Instituto Fiscal de Eduación Especial de El Oro. - Reyes Romero, Edgar Jonathan (2015)
Education changes caused by the integration of information and communications technology ICT have made that both special and regular educational institutions are interested in the use of new methodologies in the educational process. This integration makes these institutions reflect on the need to produce educational materials and training processes adapted to the new needs of the learning environment and students today. From the pedagogical point of view with regard to special education, ICT represent advantages for the teaching-learning because they allow: stimulate interpersonal communication as well as monitoring of student progress, at individual and group level, management and administration of students, creating scenarios for peer assessment and self-assessment. Attorney Special Education The Gold Institute is experiencing significant growth of students with special abilities, for this reason the implementation of a virtual learning environment using free software tools such as Moodle will make it possible to create virtual classrooms that facilitate access to information and learning content through the internet representing significant advantages for the teaching-learning because not only the teacher will intervene in this process, but parents also have an important role in teaching their children develop learning and construction social identity in a teaching-learning process student-centered and based on the development of their skills and capabilities. It should be noted that the implementation of this work degree will not only benefit students Attorney Institute of Special Education of El Oro but also the wider community you want to use it can do as it will be freely available resources provided in said virtual environment pretending thus mitigating the problem of discrimination against children with special abilities in school age entering regular schools.